Oxygen Exchange Processes between Oxide Memristive Devices and Water Molecules. Issue 29 (7th June 2018) - Heisig, Thomas; Baeumer, Christoph; Gries, Ute N.; Mueller, Michael P.; La Torre, Camilla; Luebben, Michael; Raab, Nicolas; Du, Hongchu; Menzel, Stephan; Mueller, David N.; Jia, Chun‐Lin; Mayer, Joachim; et al.
Abstract: Resistive switching based on transition metal oxide memristive devices is suspected to be caused by the electric‐field‐driven motion and internal redistribution of oxygen vacancies. Deriving the detailed mechanistic picture of the switching process is complicated, however, by the frequently observed influence of the surrounding atmosphere. Specifically, the presence or absence of water vapor in the atmosphere has a strong impact on the switching properties, but the redox reactions between water and the active layer have yet to be clarified. To investigate the role of oxygen and water species during resistive switching in greater detail, isotope labeling experiments in a N2 /H2 18 O tracer gas atmosphere combined with time‐of‐flight secondary‐ion mass spectrometry are used. It is explicitly demonstrated that during the RESET operation in resistive switching SrTiO3 ‐based memristive devices, oxygen is incorporated directly from water molecules or oxygen molecules into the active layer. In humid atmospheres, the reaction pathway via water molecules predominates. These findings clearly resolve the role of humidity as both oxidizing agent and source of protonic defects during the RESET operation. Abstract : The interaction of memristive devices with the atmosphere through operation in a N2 /H2 18 O tracer gas atmosphere combined with time‐of‐flight secondary‐ion mass spectrometry is reported in detail. Based on this experimental approach, the role of oxygen species in the atmosphere is clarified, and it is shown that the reaction with atmospheric species is an essential part of the switching mechanism.